2021
DOI: 10.1055/a-1388-6735
|View full text |Cite
|
Sign up to set email alerts
|

Real-time deep learning-based colorectal polyp localization on clinical video footage achievable with a wide array of hardware configurations

Abstract: Background and study aims Several computer-assisted polyp detection systems have been proposed, but they have various limitations, from utilizing outdated neural network architectures to a requirement for multi-graphics processing unit (GPU) processing, to validating on small or non-robust datasets. To address these problems, we developed a system based on a state-of-the-art convolutional neural network architecture able to detect polyps in real time on a single GPU and tested on both public datasets and full … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…A plausible explanation is that annotating high-and moderate-quality video frames compensated for the modest number of polyps. 20 CADx models are often developed using retrospective still images from endoscopy reports of expert endoscopists, but this inherently limits the data to one or a few images per polyp. These models may also generalize less well to nonexpert endoscopists, who may be less likely to reproduce the highquality images of experts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A plausible explanation is that annotating high-and moderate-quality video frames compensated for the modest number of polyps. 20 CADx models are often developed using retrospective still images from endoscopy reports of expert endoscopists, but this inherently limits the data to one or a few images per polyp. These models may also generalize less well to nonexpert endoscopists, who may be less likely to reproduce the highquality images of experts.…”
Section: Discussionmentioning
confidence: 99%
“…Our CNN achieved favorable results without using a confidence threshold despite a smaller sample size of polyps for training than other models. A plausible explanation is that annotating high‐ and moderate‐quality video frames compensated for the modest number of polyps 20 . CADx models are often developed using retrospective still images from endoscopy reports of expert endoscopists, but this inherently limits the data to one or a few images per polyp.…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al proposed to reduce FPs by using the median filter (which reduced the FPR from 12.5% to 6.3%), a nonlinear spatial filter that is particularly effective for eliminating salt-and-pepper noise [ 21 ]. To filter out most short flashes, Podlasek et al suggested setting a threshold of persistent time for FPs to show up; however, this method might introduce a minor detection lag, depending on the desired sensitivity [ 22 ]. These methods are beyond the expertise of the clinical endoscopists.…”
Section: How To Address the Occurrence Of Fpsmentioning
confidence: 99%
“…The F1 score of CVC-ClinicDB ranged from 0.727 to 0.942. With a 3% FP rate, full examination films sample detected 94% of polyps [9].…”
Section: Introductionmentioning
confidence: 99%
“…Different studies were concerned with developing automated systems for polyp detection. Podlasek et al [9] designed a system for polyp detection with a real-time post-processing pipeline that runs on a variety of devices. The F1 score of CVC-ClinicDB ranged from 0.727 to 0.942.…”
Section: Introductionmentioning
confidence: 99%